The Asymmetric Effect of Oil Price on the Exchange Rate and Stock Price in Nigeria - Ajala, Kamaldeen; Sakanko, Musa Abdullahi; Adeniji, Sesan Oluseyi (International Journal of Energy Economics and Policy, 2021)
The study examines the asymmetric effect of oil price on the exchange rate and stock price using the Nonlinear Autoregressive Distributive Lag (NARDL) technique on the time-series data spanning from January 1996 to September 2020. The multivariate cointegration test showed evidence of a long-run relationship among the stock price, exchange rate, and oil price. The linear Granger causality test showed that stock price is granger caused by oil price and exchange rate, and oil price is granger cause by stock price and exchange rate. The nonlinear granger causality showed evidence of nonlinearity using the BDS test. The Dick-Panchenko non-parametric and nonlinear Granger causality test in a contrary to the linear Granger causality test showed a unidirectional nonlinear causality from exchange rate to stock price at 10% level, and from oil price to exchange rate at 1% and 10% levels respectively. The result from the nonlinear ARDL revealed that change in oil price impacted asymmetrically on the exchange rate and stock price both in the short-run and long-run. The study recommends that the revenue generated from increasing oil price should be used for developing and reinstalling decayed infrastructure and oil-exporting countries should develop mechanisms and strategies that will ensure fair stability in the capital markets irrespective of the shocks in oil price. Keywords: Exchange rate, Oil price, Nonlinear model, Stock price JEL Classifications: E52, L61, F31, C32, G15 DOI: https://doi.org/10.32479/ijeep.10977